DC Respond to Cognate T Cell Interaction in the Antigen-Challenged Lymph Node - Curato, Caterina; Bernshtein, Biana; Zupancič, Eva; Dufner, Almut; Jaitin, Diego; Giladi, Amir; David, Eyal; Chappell-Maor, Louise; Leshkowitz, Dena; Knobeloch, Klaus-Peter; Amit, Ido; Florindo, Helena F.; et al. (Frontiers in Immunology, 2019)
Dendritic cells (DC) are unrivaled​ in their potential to prime naive T cells by presenting antigen and providing costimulation. DC are furthermore believed to decode antigen context by virtue of pattern recognition receptors and to polarize T cells through cytokine secretion towards distinct effector functions. Diverse polarized T helper (TH) cells have been explored in great detail. In contrast, studies of instructing DC have to date largely been restricted to in vitro settings or adoptively transferred DC. Here we report efforts to unravel the DC response to cognate T cell encounter in antigen-challenged lymph nodes (LN). Mice engrafted with antigen-specific T cells were immunized with nanoparticles (NP) entrapping adjuvants and absorbed with an antigen to study the immediate DC response to T cell encounter using bulk and single cell RNA-seq profiling. NP-induced robust antigen-specific TH1 cell responses with minimal bystander activation. Fluorescent-labeled NP allowed identification of antigen-carrying DC and focus on transcriptional changes in DC that encounter T cells. Our results support the existence of bi-directional crosstalk between DC and T cells that promotes TH1 responses, including involvement of the ubiquitin-like molecule Isg15 that merits further study.